Seasonal dynamics of coarse atmospheric particulate matter between 2.5 μm and 80 μm in Beijing and the impact of 2008 Olympic Games. (January 2016) - Norra, Stefan; Yu, Yang; Dietze, Volker; Schleicher, Nina; Fricker, Mathieu; Kaminski, Uwe; Chen, Yuan; Stüben, Doris; Cen, Kuang
Abstract: Beijing is well known as a megacity facing severe atmospheric pollution problems. One very important kind of pollution is the high amount of particles in Beijing's atmosphere. Numerous studies investigated the dynamics of fine particles smaller 10 μm. Less information is available on the coarse particle fraction larger 10 μm, although geogenic dusts, which often are composed by those coarser particles, frequently affect the air quality in Beijing. Therefore, systematic sampling and analysis of size fractionated particulate matter between 2.5 and 80 μm was performed in Beijing from April 2005 till October 2009. Atmospheric particles were collected in the North-West of Beijing using a cost-effective passive sampling method called Sigma-2. Altogether, 200 weeks could be analysed and assessed. Concentrations and size distribution of atmospheric coarse particles were determined by automated microscopic single particle analysis. Seasonal variability of the total mass of different size fractions was identified as follows: spring > winter > autumn > summer. High concentrations of transparent mineral particles indicate the activity of geogenic sources in spring and winter time, due to asian dust events and resuspension of soil from local bare land during dry and windy periods. The percentage of opaque particle components differs seasonally with relatively high values in winter, confirming combustion of fossil fuels for heating purposes as a predominant pollution source in this season. The influence of meteorological conditions on concentrations and size distribution of atmospheric particulate matter between 2.5 and 80 μm is demonstrated for the whole sampling period. Lowest pollution by coarse aerosols occurred during the period of the 2008 Olympic Summer Games. A general trend of decreasing total coarse particle mass concentrations was observed. Due to frequently observed high total coarse particle mass concentrations of several 100 μg·m − ³ it is strongly recommended to enhance research and observation regarding these air pollutants to gain a better understanding of their dynamics, health effects, well being impacts on Beijing inhabitants and the effectiveness of mitigation measures. Highlights: Assessment of coarse particles between 2.5 and 80 μm in Beijing. This study covers a long period from 2005 till 2009. Seasonal and source variations of mass concentrations are identified. Influences of Asian dust and the 2008 Olympic Games are described. A long term decrease of coarse particle mass concentrations was detected.